বৰ অসম গঢ়োতা চাওলুং ছ্যু-কা-ফা - Gogoi, Anima (T. J. Gogoi, 2017)
The book is an Assamese historical biography of first Ahom King Chowlung Siu-Ka-Fa.
Bar Axom Garhuta Chowlung Siu-Ka-Fa
Keywords: Assamese; Historical Biography; Assamese